2002
DOI: 10.2460/ajvr.2002.63.1292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraluminal distention on microvascular perfusion in the equine small colon

Abstract: Intraluminal distention of the equine small colon wall can promote ischemia by a reduction in microvascular perfusion in the intestinal wall. Intestinal layers do not seem to be affected to the same extent, because the absolute value for mucosal perfusion did not decrease in the obstructed segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
0
18
0
10
Order By: Relevance
“…This may also occur because of the lesions from intestinal ischemia/reperfusion (Bianco-Blatlles et al, 2008), and this probably occurred during the obstruction of the lumen in the animals of the present experiment. Faleiros et al (2002) reported, under similar conditions, that distension of the small colon induced pulmonary accumulation of neutrophils.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This may also occur because of the lesions from intestinal ischemia/reperfusion (Bianco-Blatlles et al, 2008), and this probably occurred during the obstruction of the lumen in the animals of the present experiment. Faleiros et al (2002) reported, under similar conditions, that distension of the small colon induced pulmonary accumulation of neutrophils.…”
Section: Discussionmentioning
confidence: 78%
“…Local anesthesia was achieved by means of the inverted "L" technique, using 2% lidocaine hydrochloride (Xilestesin, Cristália). The middle third of the jejunum was exposed through the left paracostal fossa, in a quadrupedal position, and was subjected to intramural compression of the intestinal wall by implanting an empty latex balloon in the lumen, by means of enterotomy (Faleiros et al, 2002). The balloon was then inflated with air until reaching a pressure of 12mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Delimitou-se um segmento inicial do cólon menor, aproximadamente a 50cm da transição com o cólon transverso, e realizou-se a indução da obstrução intraluminal. Seguindo o modelo descrito por Faleiros et al (2002b), o segmento exposto foi submetido à enterotomia na borda antimesentérica para colocação de um manguito de, aproximadamente, 15cm de diâmetro, acoplado a um equipo de soro com uma pêra insufladora em sua extremidade. A pressão no interior do manguito foi registrada e monitorada por meio de um fisiógrafo 5 devidamente calibrado.…”
Section: Methodsunclassified
“…A sedação foi feita com cloridrato de xilazina a 10% (Sedazine, Fort Dodge) e butorfanol (Torbugesic, Fort Dodge), administrados por via intravenosa. A anestesia local foi realizada pela técnica de "L" invertido, com cloridrato de lidocaína 2% (Xilestesin, Cristália), sendo o terço médio do jejuno exposto por meio da fossa paracostal esquerda, em posição quadrupedal, e submetido à enterotomia seguida da compressão da parede intestinal, mediante a implantação de um balão de látex vazio no lúmen (Faleiros et al 2002). O balão foi inϐlado com ar, até atingir a pressão de 12 mmHg, e retirado após quatro horas de obstrução intestinal, por laparotomia exploratória pelo ϐlanco.…”
Section: Delineamento Experimentalunclassified